Numerical Design of Ultrathin Hydrogenated Amorphous Silicon-Based Solar Cell - F. X. Abomo Abega; A. Teyou Ngoupo; J. M. B. Ndjaka (International Journal of Photoenergy)
Numerical modelling is used to confirm experimental and theoretical work. The aim of this work is to present how to simulate ultrathin hydrogenated amorphous silicon- (a-Si:H-) based solar cells with a ITO BRL in their architectures. The results obtained in this study come from SCAPS-1D software. In the first step, the comparison between the J-V characteristics of simulation and experiment of the ultrathin a-Si:H-based solar cell is in agreement. Secondly, to explore the impact of certain properties of the solar cell, investigations focus on the study of the influence of the intrinsic layer and the buffer layer/absorber interface on the electrical parameters (JSC, VOC, FF, and η). The increase of the intrinsic layer thickness improves performance, while the bulk defect density of the intrinsic layer and the surface defect density of the buffer layer/i-(a-Si:H) interface, respectively, in the ranges [109 cm-3, 1015 cm-3] and [1010 cm-2, 5×1013 cm-2], do not affect the performance of the ultrathin a-Si:H-based solar cell. Analysis also shows that with approximately 1 μm thickness of the intrinsic layer, the optimum conversion efficiency is 12.71% (JSC=18.95 mA·cm−2, VOC=0.973 V, and FF=68.95%). This work presents a contribution to improving the performance of a-Si-based solar cells.